2009
DOI: 10.1111/j.1863-2378.2008.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mastitis and Brucellosis in Cattle in Awassa and the Peri-Urban Areas of Two Smaller Towns

Abstract: The prevalence of mastitis and brucellosis in urban and peri-urban settings was studied in Awassa and two smaller nearby towns in southern Ethiopia, because milk-born diseases are causing a risk for human health, besides direct impacts on animal production. Mastitis was investigated by examining 80 cows (320 udder quarters) using California mastitis test (CMT) and somatic cell count (SCC). The prevalence of brucellosis was assessed by sampling 177 cattle in Awassa and its peri-urban areas using serological met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, there was no impact of stillbirth, swollen testes and weak calf and lambs on milk production as reported by farmers in this region. In previous studies carried out in other settings [17], it was demonstrated that mastitis suspected to be resulting from brucellosis infection led to reduction in milk production in cattle. Even though mastitis was not evaluated in the current study, the findings in the previous study is generally consistent with our observations that suspected brucellosis infection symptoms are directly related to reduced mild production.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no impact of stillbirth, swollen testes and weak calf and lambs on milk production as reported by farmers in this region. In previous studies carried out in other settings [17], it was demonstrated that mastitis suspected to be resulting from brucellosis infection led to reduction in milk production in cattle. Even though mastitis was not evaluated in the current study, the findings in the previous study is generally consistent with our observations that suspected brucellosis infection symptoms are directly related to reduced mild production.…”
Section: Discussionmentioning
confidence: 99%
“…4). These reports show that >3400 cows have been tested for clinical and subclinical mastitis in dairy herds scattered in and around Ethiopia over the past decade or so (Dego and Tareke, 2003; Sori et al , 2005; Lakew et al , 2009; Abebe et al , 2010; Bitew et al , 2010; Mekibib et al , 2010; Moges et al , 2011; Almaw et al , 2012; Daka et al , 2012; Girma et al , 2012; Haftu et al , 2012; Tadesse and Chanie, 2012; Abera et al , 2013; Belayneh et al , 2013; Yohannis and Molla, 2013; Zeryehun et al , 2013; Benti and Zewdie, 2014; Hailemeskel et al , 2014; Zenebe et al , 2014). This suggests that some African countries have higher prevalence of bovine mastitis than others, and may be more involved in dealing with disease detection, treatment and impacts than other countries.…”
Section: Reported Cases Of Clinical and Subclinical Mastitismentioning
confidence: 99%